Do people with hereditary cancer syndromes inform their at-risk relatives? A systematic review and meta-analysis - Ahsan, Muhammad Danyal; Levi, Sarah R.; Webster, Emily M.; Bergeron, Hannah; Lin, Jenny; Narayan, Priyanka; Nelson, Becky Baltich; Li, Xuan; Fowlkes, Rana K.; Brewer, Jesse T.; Thomas, Charlene; Christos, Paul J.; et al. (PEC innovation, 2023)
To evaluate rates of familial disclosure of hereditary cancer syndrome information. A systematic review and meta-analysis was conducted in accordance with PRISMA guidelines (PROSPERO no.: CRD42020134276). Key electronic databases were searched to identify studies evaluating hereditary cancer syndrome cascade relative disclosure. Eligible studies were subjected to meta-analysis. Thirty-four studies met inclusion criteria. Among 11,711 included relatives, 70% (95% CI 60 - 78%) were informed of their risk of carrying a cancer-associated pathogenic variant; of 2,875 relatives informed of their risk who were evaluated for uptake of cascade testing, 43% (95% CI 27 - 61%) completed testing. Rates of disclosure were higher among female vs male relatives (79% [95% CI 73% - 84%] vs 67% [95% CI 57% - 75%]) and first-degree vs second-degree relatives (83% [95% CI 77% - 88%] vs 58% [95% CI 45 – 69%]). Nearly one-third of at-risk relatives remain uninformed of their risk of carrying a cancer-associated pathogenic variant. Even among those informed, fewer than half subsequently complete genetic testing, representing a critical missed opportunity for precision cancer prevention. Five studies evaluating interventions to improve disclosure rates were generally ineffective. Urgent work is needed to elucidate barriers to relative disclosure by probands to develop targeted interventions that can optimize proband-mediated cascade genetic testing rates. •30% relatives are unaware of their risk of having a cancer associated pathogenic variant.•Female relatives and first-degree relatives are more likely to be informed.•Among those aware of their risk, only 43% complete genetic testing.